Analisis efektivitas kerja pada karyawan PT. Jasa Tirta Energi divisi konstruksi - Febriola, Tika; Kustini, Kustini (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of this research is to know how the influence of Workload and Work Discipline towards work effectiveness of employees in the Constructions Divisions part of PT. JASA TIRTA ENERGI with the sampling method used a saturated sample technique, which were the population as many as 37 people as the sample and also the technique analysis used for this research is operate the application namely Partial Least Square (PLS) with the try out of validity test, reliability test, and then hypothesis test. Related from the result of this research there are 1) Workload has a negative impact on employee work effectiveness 2) Work Discipline has a positive impact on the effectiveness of the employee work, which means that the highest level of awareness about work discipline from the employee so the effectivity of work is more advance.